Comparison of Imaging Characteristics of Gangliogliomas between Child/Adolescent Group and Adult Group - Zheng, Xuan; Huang, Quan; Guo, Shao-Lei; Zou, Meng-Sha; Zhu, Hui; Li, Shi-Ting (Current Medical Imaging, 2024)
Background Ganglioglioma is a rare, slowly proliferating mixed glioneuronal tumor, with the highest incidence observed in children and young adults, but it can also occur in adults. Objective This study aimed to compare the imaging characteristics of ganglioglioma in children/adolescents and adults to facilitate radiographic diagnosis. Methods In this retrospective study, a total of 32 patients were included and divided into two groups: the child/adolescent group (age < 18 years, n=19) and the adult group (age ≥ 18 years, n=13). Various variables were analyzed, including maximum diameter, location, periphery, border, calcification, unenhanced CT attenuation, T1WI, T2WI/FLAIR, and DWI signal intensity, enhancement pattern, degree of enhancement, homogeneity of enhancement, solid/cystic component, peri-tumoral edema, intra-tumoral septa, peri-tumoral capsule, and intra-tumoral hemorrhage. Results Most gangliogliomas were situated in the peripheral regions, particularly in the temporal lobe. The majority exhibited hypointense/isointense signals on T1WI and hyperintense signals on T2WI/FLAIR and DWI, with predominantly heterogeneous nodular enhancement. Peri-tumoral edema was significantly less frequent in the child/adolescent group, while marked enhancement was significantly more common in the adult group. There was no significant difference in maximum diameter between the child/adolescent group and the adult group. Conclusion Peri-tumoral edema was significantly less prevalent in the child/adolescent group, whereas marked enhancement was significantly more frequent in the adult group. To ensure accurate results, a larger case series should be conducted to validate our findings.
Keywords: Ganglioglioma